Pengaruh Perilaku Konsumtif, Gaya Hidup, dan Pendapatan terhadap Perilaku Pengelolaan Keuangan (Studi Kasus Pada Pekerja Wanita di Kota Semarang) - Oktaviani, Regina; Indriasari, Ika; Meiriyanti, Rita (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2025)
This study was conducted to determine the influence of consumptive behavior, lifestyle, and income on financial management behavior among female workers in the city of Semarang. The research employed a quantitative approach. The population consisted of female workers in Semarang. Data were collected from 115 respondents using a questionnaire. The data were processed using SPSS version 25. The research findings revealed that: (1) Consumptive behavior does not affect the financial management behavior of female workers in Semarang; (2) Lifestyle influences the financial management behavior of female workers in Semarang; (3) Income influences the financial management behavior of female workers in Semarang. The conclusion of this study is that consumptive behavior, lifestyle, and income collectively account for 45% of the variance in financial management behavior, while the remaining 55% is influenced by other factors not included in this linear regression model.